Sentidos da experiência universitária para jovens bolsistas do ProUni - Brescia Franca Nonato (2012)
This study is the result of a research developed with young academics which came from popular social classes who placed themselves into a Private University through the University Program for All (ProUni). This study aimed to comprehend the meanings of those academics experiences, considering theoretical references of young sociology and the educational sociology. The qualitative study had as methodological tool, semistructured interviews. There were interviewed 10 students, 5 from the psychology course and 5 from PUC Minas engineering courses, during at least 3-6 months the whole process. The methodological choice was based on Bernard Lahires literature, specially inspired on his work titled Retratos sociológicos. In order to better contextualize the collected data, there has been done a bibliographic review about the process of youth schooling, educational politics directed to the expansion of high school and college education system in Brazil as well as the access and staying of students from the popular social classes on the college education system in Brazil, including as well an analyses concerning samples and documents from MEC and IPEA that could contribute to the reflection about the different meanings attributed to the academic experience. It became evident that the meaning of the academic experiences are distinct, varying according to the subject and the context. However, the singular histories allow us to reflect upon the general configuration of the new public that is engaged in the superior education system.